Geological and SHRIMP II U-Pb constraints on the age and origin of the Breves Cu-Au-(W-Bi-Sn) deposit, Carajas, Brazil - Tallarico, F.; McNaughton, Neal; Groves, D.; Fletcher, Ian; Figueiredo, B.; Carvalho, J.; Rego, J.; Nunes, A. (Springer, 2004)
The Breves deposit in the Carajas Copper-Gold Belt, Brazil, a member of the Cu-Au-(W-Bi-Sn) group of deposits, contains about 50 Mt of 1.22% Cu,0.75 g/t Au, 2.4 g/t Ag, 1,200 g/t W, 70 g/t Sn, 175 g/tMo and 75 g/t Bi. It is hosted by sandstones and siltstones of the A guas Claras Formation (minimum age of 2,6815 Ma) in the roof zone of a complex, highly altered granite intrusion. The mineralisation is disseminated in a greisenized zone, resulting from alteration of probable monzogranites and syenogranites.The ore-bearing greisen contains abundant xenomorphic quartz in association with Fe-chlorite and muscovite. The gangue assemblage also includes fluorite, tourmaline, and minor amounts of monazite, xenotime, chlorapatite, thorite, zircon, calcite, siderite and bastna esite. Copper mineralisation is dominated by chalcopyrite associated with pyrite, arsenopyrite, pyrrhotite and molybdenite. Gold particles, in equilibrium with native bismuth, are common as inclusions in chalcopyrite. The greisen contains sub-economic concentrations of tungsten and niobium that are related to the presence of ferberite, qitianlingite and Nbrutile. SHRIMP II zircon dating of the host granites gives 207Pb/206Pb ages of 1,8788 and 1,8809 Ma for two phases, and a combined age of 1,8796 Ma. SHRIMP II dating of monazite and xenotime grains in late- to post-mineralisation veins gives a combined 207Pb/206Pb age of 1,8727 Ma, indistinguishable from the ages of the granites. This provides a genetic connection between the Breves deposit and the ca.1.88 Ga A-type granite magmatism that typifies the Caraja s Belt as part of a much larger, intracratonic magmatic province that extends over much of the Amazonian Craton. The recognition of this association has exploration implications, not only for the geophysical signature of the granite roof zones, but also for likely geochemical dispersion around the deposits of this type.